HISTORY OF DEVELOPMENT OF PARALYMPIC SPORTS COMPETITIONS IN UZBEKISTAN - Quvvatov Umid Tursunovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the history of the origin of Paralympic sports competitions and information about the participation of the Republic of Uzbekistan as an independent state, the results achieved and the conditions created for Paralympic athletes by the state and government of the Republic of Uzbekistan are included in it. The information in this article serves as one of the main sources for specialists and students of the educational direction of Physical Culture.